2022
DOI: 10.3390/antiox11071227
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoid-Rich Extract of Dillenia indica L. Bark Displays Antidiabetic Action in Insulin-Resistant C2C12 Cells and STZ-Induced Diabetic Mice by Attenuation of Oxidative Stress

Abstract: Insulin resistance (IR) plays a key role in the pathogenesis and clinical outcome of patients with multiple diseases and diabetes. In this study, we examined the antidiabetic effects of a terpenoid-rich extract from Dillenia indica L. bark (TRDI) in palmitic acid-induced insulin resistance (PA-IR) in C2C12 myotube and a streptozotocin (STZ)-induced diabetic mice model and explored the possible underlying mechanism. TRDI showed potential DPPH- and ABTS-radical scavenging effects with a half-maximal inhibitory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Our results support previous studies showing that antioxidant activities of various seaweed extracts and their constituents are due to activation of the Nrf2/HO-1 signaling (Jayawardena et al, 2018;Kang et al, 2015;Lekshmi et al, 2019;Niu et al, 2020;Park et al, 2018). Our results are also in good agreement with those of previous studies showing that Nrf2mediated activation of HO-1 in myoblasts can act as a protective mechanism against apoptosis induced after mitochondrial dysfunction caused by oxidative stimulation (Li et al, 2020;Park et al, 2021;Song et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…Our results support previous studies showing that antioxidant activities of various seaweed extracts and their constituents are due to activation of the Nrf2/HO-1 signaling (Jayawardena et al, 2018;Kang et al, 2015;Lekshmi et al, 2019;Niu et al, 2020;Park et al, 2018). Our results are also in good agreement with those of previous studies showing that Nrf2mediated activation of HO-1 in myoblasts can act as a protective mechanism against apoptosis induced after mitochondrial dysfunction caused by oxidative stimulation (Li et al, 2020;Park et al, 2021;Song et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…Ge et al. [ 43 ] showed that the spinosin could ameliorate the insulin resistance of high‐fat diet mice. Besides, there are other literatures showed the hypoglycemic activities of jujuboside A.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the IC 50 values of SZJs and acarbose against 𝛼-glucosidase and 𝛼-amylase are shown in Table 2, the results indicated that the SZJ- [40] , Kim et al, [41] and Song et al [42] have revealed the betulinic acid from Dillenia indica L. could increase the glucose-stimulated insulin secretion in insulinoma cells, and ameliorate hyperglycemia of high-fat diet fed mice. Ge et al [43] showed that the spinosin could ameliorate the insulin resistance of high-fat diet mice. Besides, there are other literatures showed the hypoglycemic activities of jujuboside A.…”
Section: Inhibitory Effects On 𝜶-Glucosidase and 𝜶-Amylasementioning
confidence: 99%
“…In this study, the terpenoid group of compounds is also abundant in ethanolic Boeau macrophylla, which possesses various health benefits. For instance, the previous study demonstrated that terpenoids or isoprenoid display antidiabetic action in mice [ 13 ] and also exhibit cytotoxicity against tumour cells [ 14 ].…”
Section: Discussionmentioning
confidence: 99%